Effectiveness of desensitizing dentifrice and mouthwash on dentin hypersensitivity and tooth remineralization - Shweta Sharda; Kakarlap V. V. Prasad; Preetha J Shetty; Krithi Nikhil (Wolters Kluwer Medknow Publications, 2018)
Background: Over many years, numerous products have been suggested for the relief of dentin hypersensitivity (DH). Calcium sodium phosphosilicate is one desensitizing agent that has remineralizing potential. Available in toothpaste and mouthwash delivery vehicle, this study was carried out to compare the effectiveness on dentinal hypersensitivity (using the Airblast test and Cold test) and on tooth remineralization (using DIAGNOdent pen) in a 4-week period. Materials and Methods: Out of the 45 patients screened, 28 patients who fulfilled the inclusion criteria and who willingly signed the consent form were selected and were randomly allocated into two groups - toothpaste and mouthwash. The tooth numbers and specific site of dentinal hypersensitivity for every patient were noted and the air blast test, cold test, and DIAGNOdent scores were recorded at baseline visit. The patients were instructed about the use of the product and were asked to come on the 30th day for re-evaluation. Results: Within-group comparison showed a significant reduction (P < 0.05) in the air blast score (toothpaste - 68.53% and mouth rinse - 48.52%), cold test score (toothpaste - 56.38% and mouth rinse - 38.87%), and DIAGNOdent score (toothpaste - 20.35% and mouth rinse - 9.49%). In-between group comparison showed no statistically significant difference (P > 0.05). Conclusion: Desensitizing mouthwash is as effective as toothpaste in reducing DH with a fair remineralization potential comparable with that of the toothpaste.